Cyberwarfare: A Constructivist Analysis Towards the United States-China Cyberwar - Mulia, Jalaluddin Rizqi (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Cyberspace is a discussion not merely related to technological advancements, but also penetrates the socio-political realm. Cyber issues are now starting to overwhelm security isue with the spread of cyberattacks. Although only happening in cyberspace, the impact resulting from the action can be fatal for major infrastructures in the real world, icluding data management, public private information, and the state security system. This is what happened between the United State (US) and China. Beforehand, the US and China had an agreement in cyberspace issues to develop international norms. Nonetheless, this step was not significant given the reluctance of both parties to implement the points of agreement as they were not in line with the national interest. In addition, the two countries often accuse each other of cyberrattacks occurring in their respective territories. As the world's two strong cyber powers, the process of cyberwar becomes urgent to be analyzed through the constructivism concept, as it takes identity understanding into account. By utilizing descriptive qualitative approach through literature study, this research aims to understand the cyberspace situation between the US and China and to analyze the ongoing process of the US-China cyberwar from a constructivism perspective. Social construction plays an important role as it shapes perceptions of other actors. With China, it is difficult for the US to form sustainable cooperation given the fluctuating dynamics of the relationship between the two. Until the end, it is currently difficult to find similarities that would reduce the tension of political conflict.